Percepção da paisagem urbana do bairro Liberdade (São Paulo - SP): a perspectiva das diferentes gerações nipo-brasileiras frente às transformações urbanas - Dias, Renata Felício Boitar Paes [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This work aims to understand the effect of the changes in the urban landscape of the Liberdade neighborhood upon cultural identity of Brazilian-Japanese community, through the perspective of the perception of the landscape of different Japanese-Brazilian generations. Therefore, it primarily considered that the landscape is, by nature, successively transformed, presenting itself distinctively and filled by different values, feelings, memories, and symbols to each individual. In the Liberdade neighborhood, a new phase began since the sixties, with the intense process of urbanization in the city of São Paulo, where the insertion of the Liberdade and São Joaquim subway stations resulted in several changes, such as the growth of local trade, increase in the flow of people and the establishment of Chinese and Korean colonies. It is within this context of changes that the research is inserted, in order to find out about new meanings and values from the perception of the neighborhood urban landscape, making the product of this investigation an important tool for planning and managing the neighborhood in the present and in the future. In the methodological step, the performed fieldworks allowed for photographic records, observations and characterization of the current neighborhood landscape. In order to assimilate the perception of the neighborhood urban landscape, it was developed a set of seven questions, directed to individual experiences and perspectives, aimed at Isseis and descendants of Japanese who were familiar with the Liberdade neighborhood, consisting of two groups; an age group of 18-35 years olds and another one, of over 35 years olds. In this work, a humanistic approach was chosen, from the perspective of phenomenology that values perception and individual experience in the description of a phenomenon. As results, the neighborhood landscape faced a dual character transformation, which has generated subproducts to the present day, such...

O presente trabalho buscou compreender o efeito das transformações na paisagem urbana do bairro Liberdade sobre a identidade cultural da comunidade nipo-brasileira sob a perspectiva da percepção da percepção da paisagem pelas diferentes gerações. Para tanto, partiu-se da consideração de que a paisagem é, por natureza, sucessivamente transformada, apresentando-se distinta e carregada de diversos valores, sentimentos, lembranças, e símbolos para cada indivíduo. No bairro da Liberdade, uma nova fase iniciou-se a partir da década de 60, com o intenso processo de urbanização na cidade de São Paulo, onde a inserção das estações Liberdade e São Joaquim do metrô acarretou em diversas transformações, como crescimento do comércio local, aumento no fluxo de pessoas e a entrada das colônias chinesa e coreana. É dentro desse contexto de mudanças que a pesquisa se insere, com o intuito de averiguar novos significados e valores na percepção da paisagem urbana local, sendo o produto dessa investigação um importante instrumento de planejamento e gestão do bairro no presente e futuro. A realização dos trabalhos de campo compreendeu registros fotográficos, observações e caracterização da paisagem atual do bairro. A fim de apreender a percepção da paisagem urbana do bairro foi elaborado um conjunto de sete questões, direcionadas às experiências e perspectivas individuais, destinadas a isseis e descendentes de japoneses que tivessem familiaridade com o bairro Liberdade, constituindo dois grupos; um de faixa etária de 18 a 35 anos e o outro, acima de 35 anos. Neste trabalho, optou-se por uma abordagem humanista sob a óptica da fenomenologia que valoriza a percepção e experiência individual na descrição de um fenômeno. Como resultados, pudemos observar que a paisagem do bairro passou por transformações de duplo caráter que geraram subprodutos até os dias atuais, como aumento da violência, aumento do número de...
Keywords: Geografia humana; Urbanização; Planejamento urbano; Memória coletiva; Nipo-brasileiros; Gerações; Imigrantes; São Paulo (SP)